ЛИРИКАЛЫҚ ПОЭМАЛАРДА СЮЖЕТ ҲӘМ КОМПОЗИЦИЯНЫҢ ЛИРИКАЛЫҚ ҚАҲАРМАН ОБРАЗЫН ЖАСАЎДАҒЫ ӘҲМИЙЕТИ (К.Рахмановтың «Сен ҳаққында қосық», Т.Мәтмуратовтың «Перийзат» поэмалары мысалында) - Дабылов, П.А. (FAN va JAMIYAT, 2017)
The article deals with the analysis of questions of plot, composition and character in the 1yrical poems of the famous Karakalpak poets K.Rakhmanov, and T.Matmuratov In the focus of attention is the study of the role of plot and composition in forming the characters of heroes in the poem and the genre peculiarities of the poem.